2015
DOI: 10.1542/peds.2013-4037
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Pediatric Herpes Zoster After Varicella Infection: A Population-Based Study

Abstract: There are limited population-based data regarding pediatric herpes zoster (HZ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
43
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 27 publications
0
43
0
Order By: Relevance
“…This indicates that infants are likely to be protected by herd immunity. Given that varicella infection during infancy is associated with higher mortality and a greater frequency of herpes zoster infection in childhood, [29][30][31][32] vaccination may help prevent long-term complications as well. This study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that infants are likely to be protected by herd immunity. Given that varicella infection during infancy is associated with higher mortality and a greater frequency of herpes zoster infection in childhood, [29][30][31][32] vaccination may help prevent long-term complications as well. This study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…have reported, however, that HZ incidence has increased in children 10–19 years of age and decreased in younger children . Moreover, a recent population‐based study from Taiwan reported that, after Varicella vaccination implementation, children diagnosed with Varicella between the ages 2 and 8 years had a significantly increased incidence of HZ compared with that observed before the vaccination program …”
Section: Discussionmentioning
confidence: 99%
“…10 Moreover, a recent population-based study from Taiwan reported that, after Varicella vaccination implementation, children diagnosed with Varicella between the ages 2 and 8 years had a significantly increased incidence of HZ compared with that observed before the vaccination program. 7 Field experts had initially expressed concerns, that HZ incidence rates would increase notably in persons with pre-existing natural immunity within the first 30 years following the implementation of universal Varicella immunization. 5,6 The initially anticipated effects of universal Varicella immunization on HZ incidence rates, however, may have underestimated the effects of endogenous boosting, as well as of the exposure of naturally immune subjects to Varicella by HZ patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations